2011
DOI: 10.1177/0956797611429467
|View full text |Cite
|
Sign up to set email alerts
|

Is the Map in Our Head Oriented North?

Abstract: We examined how a highly familiar environmental space--one's city of residence--is represented in memory. Twenty-six participants faced a photo-realistic virtual model of their hometown and completed a task in which they pointed to familiar target locations from various orientations. Each participant's performance was most accurate when he or she was facing north, and errors increased as participants' deviation from a north-facing orientation increased. Pointing errors and latencies were not related to the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
85
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(101 citation statements)
references
References 20 publications
13
85
3
Order By: Relevance
“…However, as we point out in the supplementary material, unreported data from another experiment (Frankenstein et al, 2012) suggest, first, that location perspective recall of configurations is also observed in a map-drawing task and at a somewhat remote location (the distance test location-city center-was similar to that in another study that had observed default recall: Basten et al, 2012). This makes sense, since the plaza layout was likely learned from local navigational experience.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…However, as we point out in the supplementary material, unreported data from another experiment (Frankenstein et al, 2012) suggest, first, that location perspective recall of configurations is also observed in a map-drawing task and at a somewhat remote location (the distance test location-city center-was similar to that in another study that had observed default recall: Basten et al, 2012). This makes sense, since the plaza layout was likely learned from local navigational experience.…”
Section: Discussionsupporting
confidence: 60%
“…This explanation by view preactivation cannot hold for the present experiment. Configurational knowledge-specifically, within Tübingen-is represented within a single north-up reference frame (Frankenstein et al, 2012), not within a graph structure (Meilinger, Frankenstein, & Bülthoff, 2013) suited for activation spread. Furthermore, activation spread would predict no influence of body orientation, which we, however, observed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations